(U‐Th)/He zircon dating of Chesapeake Bay distal impact ejecta from ODP site 1073. (21st June 2019) - Biren, M. B.; Wartho, J.‐A.; VAN Soest, M. C.; Hodges, K. V.; Cathey, H.; Glass, B. P.; Koeberl, C.; Horton, J. W.; Hale, W.
Abstract: Single crystal (U‐Th)/He dating has been undertaken on 21 detrital zircon grains extracted from a core sample from Ocean Drilling Project (ODP) site 1073, which is located 390 km northeast of the center of the Chesapeake Bay impact structure. Optical and electron imaging in combination with energy dispersive X‐ray microanalysis (EDS) of zircon grains from this late Eocene sediment shows clear evidence of shock metamorphism in some zircon grains, which suggests that these shocked zircon crystals are distal ejecta from the formation of the 40 km diameter Chesapeake Bay impact structure. (U‐Th/He) dates for zircon crystals from this sediment range from 33.49 ± 0.94 to 305.1 ± 8.6 Ma (2σ), implying crystal‐to‐crystal variability in the degree of impact‐related resetting of (U‐Th)/He systematics and a range of different possible sources. The two youngest zircon grains yield an inverse‐variance weighted mean (U‐Th)/He age of 33.99 ± 0.71 Ma (2σ uncertainties n = 2; mean square weighted deviation = 2.6; probability [ P ] = 11%), which is interpreted to be the (U‐Th)/He age of formation of the Chesapeake Bay impact structure. This age is in agreement with K/Ar, 40 Ar/ 39 Ar, and fission track dates for tektites from the North American strewn field, which have been interpreted as associated with the Chesapeake Bay impact event.